Two New Splitting Methods for Three-Operator Monotone Inclusions in Hilbert Spaces - Nguyen, Van Dung; Vinh, Nguyen The (Set-valued and variational analysis, 2024)
In this paper, we propose two new unified splitting methods for monotone inclusion problems with three operators in real Hilbert spaces. These methods are based on the combination of Douglas-Rachford method and other methods, forward-backward-forward method and reflected-forward-backward method. The weak convergence of new algorithms under standard assumptions is established. We also give some numerical examples to demonstrate the efficiency of the proposed methods.